Pengaruh Pelatihan dan Penempatan Kerja terhadap Kinerja Karyawan Bank Pembiayaan Rakyat Syariah Bangka Belitung Cabang Koba Kabupaten Bangka Tengah - Riska Aprilia; Hendra Cipta; Riyani Fitri Lubis (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2023)
Performance is an important aspect in managing employees in a company, this is because companies need employees who have quality and are competent in their fields to achieve the goals of an organization. One form of activity carried out by the company is to conduct job-related training to increase knowledge and job placement with different levels of competency. This research aims to determine the effect of Training and Job Placement on Employee Performance both partially and simultaneously. This research uses Human Resource Management theory related to employee performance. This research is field research with a quantitative approach. The population in this study were employees of the Bangka Belitung Sharia People's Financing Bank, Koba Branch, Central Bangka Regency, totaling 30 respondents. The sampling technique uses saturated sampling in which all members of the population are sampled. The data sources used in this research are primary data and secondary data. Primary data is obtained from the results of respondents' answers via questionnaires, while secondary data is obtained from information collected as necessary supporting data. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression testing and hypothesis testing. The research results based on the t test show that the training variable and work placement variable have a positive and significant effect on employee performance. This is proven by the training factor which obtained a tcount value of 7.906 > ttable 2.048 with a sig level of 0.000 < 0.05. Meanwhile, the job placement factor obtained was tcount 5.560 > ttable 2.048 with a sig level of 0.000 < 0.05. The research results based on the F test show that training variables and work placement variables have a positive effect on employee performance with a Fcount value of 153.184 > Ftable 4.21 with a sig level of 0.000 < 0.05. The R Square value obtained was 95.9%, while the remaining 4.1% was influenced by other variables not examined in this research.